2017
DOI: 10.1017/s0263574717000546
|View full text |Cite
|
Sign up to set email alerts
|

Sit-to-stand and stand-to-sit assistance for paraplegic patients with CUHK-EXO exoskeleton

Abstract: SUMMARYIn this paper, we introduce a lower extremity exoskeleton CUHK-EXO that is developed to help paraplegic patients, who have lost the motor and sensory functions of their lower limbs to perform basic daily life motions. Since the sit-to-stand and stand-to-sit (STS) motion is the first step for paraplegic patients toward walking, analysis of the exoskeleton's applicability to the STS motion assistance is performed. First, the human-exoskeleton system (HES) is modeled as a five-link model during the STS mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Effects. SCI, one of the main causes of mobility disorders, affects around 0.25-0.5 million people every year around the world especially the young [98]. Approximately 43% of SCI patients turn out to have paraplegia and the number is increasing year by year [99].…”
Section: Knee Neurological Disorders and Its Biomechanicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects. SCI, one of the main causes of mobility disorders, affects around 0.25-0.5 million people every year around the world especially the young [98]. Approximately 43% of SCI patients turn out to have paraplegia and the number is increasing year by year [99].…”
Section: Knee Neurological Disorders and Its Biomechanicalmentioning
confidence: 99%
“…The SCI patients are at an increasing risk of many secondary medical complications, including muscle atrophy, pressure ulcer, bone density reduction, and osteoporosis [100,101]. Standing and walking, as the most prevalent desires of these patients, can stimulate blood circulation, ease muscle spasm, and increase the bone mineral density [98,102]. Some evidences showed that the SCI patients can reduce the secondary medical complications risk and recover motion capabilities by standing or walking for several hours per day [98,99,102,103].…”
Section: Knee Neurological Disorders and Its Biomechanicalmentioning
confidence: 99%
“…Furthermore, using a multi-sensor network, ERs can collect a patient's movement intention and perfectly cooperate with the user's motion. Also, it can provide external force or torque to the user's legs under control, consequently yielding user-initiated movability (Chen et al, 2017a , b , 2018 ). The inability to engage in the voluntary movement has likely had several detrimental effects on people's ability to improve their lifestyles in the past and still does so today.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [4] present a self-adaptive control strategy used on lower limb exoskeleton to help paraplegic patients to SU and SD, but its speeds are slower than joints of normal people. Chen et al [5,6] present a wearable exoskeleton suit (CUHK-EXO) to help paralyzed patients regain the ability to walk, SU and SD. Safety tests for long-term wearing of CUHK-EXO will also be conducted in the future, including any adverse effect in the hip, groin, penis, back, wrist, glutei, and scapula of the wearers.…”
Section: Introductionmentioning
confidence: 99%